2021
DOI: 10.47405/mjssh.v6i4.728
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Needs for the Development of Organic Reaction Teaching Model: Experts’ Collective Opinion

Abstract: This article reported the findings of a study carried out to investigate the need for developing an organic reaction mechanism teaching model. Qualitative data was obtained through a semi-structured interview among five chemistry subject matter experts to explore their opinion on the issues centered on the teaching and learning of organic reaction mechanisms. The interviews were interpreted and analyzed using thematic analysis. Five themes comprising of many codes and quotations were identified. The analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Experts who are lecturers in Organic Chemistry were also selected as participants because the content of the article meets the inclusion criteria of the study. reactions (Flynn & Ogilvie, 2015;Bhattacharyya & Harris, 2018;Crandell et al, 2018;Webber & Flynn, 2018; Bongers, Northoff & Flynn, 2019;Sabitu et al, 2021). In Webber and Flynn (2018), they found that EPF is a useful tool for students in solving ORM problems, whereas they can determine plausible steps through EPF successfully.…”
Section: A Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experts who are lecturers in Organic Chemistry were also selected as participants because the content of the article meets the inclusion criteria of the study. reactions (Flynn & Ogilvie, 2015;Bhattacharyya & Harris, 2018;Crandell et al, 2018;Webber & Flynn, 2018; Bongers, Northoff & Flynn, 2019;Sabitu et al, 2021). In Webber and Flynn (2018), they found that EPF is a useful tool for students in solving ORM problems, whereas they can determine plausible steps through EPF successfully.…”
Section: A Study Characteristicsmentioning
confidence: 99%
“…Moreover, Dood et al (2020) stated that online systems would perform better on assessments as compared to the textbook, which provides a positive impact on students' mastery of the subject studied. Meanwhile, an animated video seem recommended by most authors because, through visualisation, the curve arrow in mechanism reaction shows the dynamic changes to how electrons and bonds are represented, yet the video can be viewed repeatedly at any time to point outs the correct steps of mechanisms (O'Brien-Tomory, 2016; Bongers, Northoffand Flynn, 2019;Winter et al, 2019;Sabitu et al, 2021). Furthermore, 11 from 17 studies had discussed automatic feedback or automated scoring as effective tools in supporting students' learning.…”
mentioning
confidence: 99%